A Novel Non Linear Distortion Suppressed, Pre-Compensation for A 10.7-Gb/S System Employing A Directly Modulated Laser (International Journal of Engineering and Computer Science, 2015)
A Novel Framework for investing the electronic compensation for a 10.7-Gb/s system using a directlymodulated LASER (DML) approach. The significant usage of digital signal processing and large signal rateequations helps in reducing the non linear distortion which outcomes from direct modulation of laser and togenerate an appropriate modulating current. After successful generation of modulation current the proposedscheme is then utilized in a novel look up table optimization scheme for electronic dispersion precompensation.Finally the simulation results shows that the proposed theoretical work shows thecompensation of 250km approximately using a 21.4GSa/s DIGITAL TO ANALOG CONVERTER andsimultaneously 350km approximately using a 42.8GSa/s DAC. Finally the proposed work shows thatapproximately using a 42.8GSa/s DIGITAL TO ANALOG CONVERTER is sufficient forexploiting the fullpotential for ELECTRONIC PRE-COMPENSATION using a DML.